Schools as learning organisations: towards a proposed model or organisational development to enhance teaching - Calaca, Rosa (My University, 2014)
This research focuses on the influence of organisational structures on teaching in schools. It does this through an analysis of teachers’ perceptions of the influence of the organisational structure on their teaching. The creative tension is created between where people perceive themselves presently and where they wish to be, that is within a framework that is conducive to a culture of teaching and learning. It is contended that, in a changing environment, traditional organisational structures are not meeting the need for ongoing change and adaptation. In the past schools were characterised by hierarchical structures which focused on control and the maintenance of order. While such structures may have been appropriate in tiiis paradigm, there is now definite pressure for change. The new paradigm demands a complete rethink about the structure of organisations so that learning is enhanced. The concepts of a Learning Organisation and Catholic School Renewal present a response to the changing needs of schools. A Learning Organisation raises many challenges which need to be explored as an organisational structure that will enhance teaching and learning. Building learning organisations, we are discovering, requires basic shifts in how we think and interact The changes go beyond individual corporate cultures, or even the culture of Western management; they penetrate to the bedrock assumptions and habits of our vulture as a whole. (Kofman & Senge 1993,5)
Thesis (M.Ed.)--University of the Witwatersrand, Faculty of Education, 1999.